Investigating effects of interpass time during hot finish rolling on the evolution of texture in AA3104 Can Body Stock - Chaole, Nkopo (Department of Mechanical Engineering, 2025)
During the hot rolling of aluminium strips, inter-pass time variability along the strip length leads to non-uniform microstructure and texture development, which impacts material properties. This study investigated the microstructure and texture evolution in AA3104 can body stock (CBS) during hot finish rolling by simulating multi-pass, high-temperature plane strain compression tests on a Gleeble 3800. Two scenarios were simulated: Position A, with a longer inter-pass time between the first two passes and a shorter time before the third pass, and Position B, with reversed timings. Post-deformation, samples were annealed and analysed using Scanning Electron Microscopy (SEM) and Electron Backscatter Diffraction (EBSD). Results indicate Position A exhibits smaller and larger grains, while Position B shows uniform grain size distribution. Texture analysis reveals stronger Cube texture in Position A and Goss and P texture dominance in Position B. These variations highlight the role of inter-pass time in recrystallisation behaviour, influencing grain structure and texture during hot rolling.